Pre Number Sense Learning for Autistic Children - Damayanti, Nia Wahyu; Kusuma Putri, Andri Nur; Carli, Ali (International Journal of Trends in Mathematics Education Research, 2025)
This study aims to explore the understanding of number sense among children with autism. Developing student intelligence is non-negotiable, as it enables them to compete at an international level. Equally important is the need to support these students in reaching their full potential, so they may live independently, take responsibility, and contribute as active citizens just like typically developing children. At the foundation of learning mathematics lies the understanding of basic number concepts, or pre-number sense. This study utilized an observational method based on the 3M approach: writing, choosing, and stating. The basic numbers tested with the autistic student ranged from 1 to 4. The child in this study exhibited motor impairments, which significantly affected performance particularly in the writing and stating tasks. The results showed that the student was unable to respond correctly using these methods, highlighting the need for adaptive strategies in early numeracy instruction for autistic learners.